General conception of the studies of mathematics and their successful realization at Vilnius Pedagogical University - Jonas Banys; Liucija Griniuvienė; Vanda Naudžiūnienė (Lietuvos Matematikos Rinkinys)
In this paper enrolment and study problems in the faculty of Mathematics and informatics of Vilnius Pedagogical university are discussed.